Pola Konsumsi Makanan Jajanan Dan Status Gizi Anak Sekolah Dasar Di SD N 17 Dangin Puri Dan SD N 3 Penatih Kota Denpasar - Made Pathya Danti Purnawijaya; I Putu Suiraoka; Hertog Nursanyoto (Jurusan Gizi, Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2018)
Some nutritional problems are still experienced by school-age children in Indonesia. School snack contribute to the daily energy needs of children, which reached 20% - 31.1%. This study aims to determine the pattern of consumption of snack foods and nutritional status of primary school children. Data collected using 24 hour recall form performed 2 times. Descriptive analysis of frequency distribution tables and interrelationships among variables were analyzed using cross tables. Most of the samples had normal nutritional status (62.5%) and (55.3%). Type of food snack in SD N 17 dangin Puri is in the category less (75.0%), while in SD N 3 Penatih most are in good category (65.8%). Energy consumption in both schools is in good category (57.5%) and (73.7%). Protein consumption in both schools was in good category (62.5%) and (73.7%). After analyzed descriptively obtained result at SD N 17 Dangin Puri that is tendency there is correlation between type of food snack and nutritional status. While in SD N 3 Penatih there is no tendency of linkage between type of food snack and nutritional status. Results in SD N 17 Dangin Puri and SD N 3 Penatih showed that there was a tendency of interrelationship between nutritional value of snack and nutritional status. There are still nutritional problems in both elementary schools, so it is advisable for the school and parents to better control the food intake of children.Keywords: Pattern of Food Consumption, Nutritional Status, Child in Elementary School